Teacher Identity in CLIL: A Case Study of Two In-service Teachers - Patricia Bárcena Toyos (Universidad de La Sabana, 2022)
The provision of CLIL teachers in Spain has outpaced the growth of the so-called bilingual programs, as there are no specific training requirements for CLIL teachers who are either content or language specialists. So, CLIL teachers have a preexistent teacher identity that could influence their pedagogical choices. This study examines how teachers negotiate their existing teacher identities in a CLIL environment and how they exercise those identities in the classroom. The study adopts a qualitative case study methodology using interviews and questionnaires. Findings show that the way teachers negotiated their identities was affected by their former personal and professional experiences, their conceptualization of the imagined community, and their investment in that community. The findings have implications for creating in-service training programs that enhance teachers' language awareness in CLIL and their association with the community.